Interferon Induction by the Psittacosis Agent in Guinea Pig Leukocyte Cultures - Kozikowski, Edmund H. (1970)
High titers of interferon were induced by the psittacosis agent in guinea pig leukocyte cultures. Optimal yields of interferon were produced from freshly prepared guinea pig leukocyte cultures containing 4 × 10(6) cells per ml inoculated with a psittacosis/cell multiplicity of 1.0 and incubated at 35 C for 24 hr. Leukocytes obtained from 2- to 4-month-old guinea pigs produced 20 times more interferon than leukocytes from 3- to 4-week-old animals. The biological activity of interferon and the kinetics of its production from psittacosis-infected guinea pig leukocyte cultures were similar to those reported for virus-induced leukocyte interferons.